(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Terrorism poses unique challenges to the liberal democratic state. Bound by rule of law and its due process, democratic regime cannot resort to the same bloody methods used against it, in combating terrorism. The vulnerability of democracy to terrorism is the focus of the article.